Potential of airborne LiDAR data for terrain parameters extraction. (20th February 2021) - Sharma, Mayank; Garg, Rahul Dev; Badenko, Vladimir; Fedotov, Alexandre; Min, Liu; Yao, Ada
Abstract: LiDAR (Light Detection and Ranging) remote sensing is the most popular technology delivering higher detailed information and accuracy. LiDAR data is majorly used for generating a high-resolution digital elevation model (DEM), which is one of the primary data for most of the remote sensing applications. DEM forms the basis to derive other terrain parameters that are important to understand the topographic variations for the majority of applications. This research work highlights the potential of airborne LiDAR data for the extraction of terrain parameters. The airborne LiDAR dataset used in this study is of the St. Petersburg region of Russia. Terrain parameters like digital surface model (DSM), bare earth model (BEM), slope, aspect, curvature and terrain ruggedness index (TRI) are estimated from the airborne LiDAR data. Ground control points surveyed using Differential Global Positioning System (DGPS) technique are used to assess the accuracy of the generated digital elevation model. An RMSE of 1.30 cm is obtained for the generated DSM with a maximum error of 3.5 cm magnitude. A complete analysis of derived parameters is done to observe the accuracy achieved.